2021
DOI: 10.1080/20477724.2020.1845479
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to disinfectants (chlorhexidine and isopropanol) and its association with antibiotic resistance in clinically-relatedKlebsiella pneumoniaeisolates

Abstract: Disinfectants play an essential role in controlling the dissemination of bacteria in health care settings, but it may also contribute to the selection of antibiotic resistance bacteria. This study looked at Klebsiella pneumoniae isolates collected from three hospitals in Lima, Peru, in order to evaluate: their susceptibility to chlorhexidine [CHG] and isopropanol [ISP]), and their association with antimicrobial susceptibility. We analyzed 59 K. pneumoniae isolates and assessed their CHG and ISP susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…For alcohol-based disinfectants, reports have claimed no cross-resistance between DAs and antibiotics (Kampf, 2018a , b ). This is supported by a recent study of Morante et al ( 2021 ) which found no relation in Klebsiella pneumoniae isolates resistant to isopropanol and antibiotic resistances. This is contrary to de Carvalho et al ( 2020 ) who showed that Mycobacterium vaccae were more resistant to antibiotics after disinfectant exposure.…”
Section: Resistance To Disinfectants and Antiseptics And Cross-resist...supporting
confidence: 66%
“…For alcohol-based disinfectants, reports have claimed no cross-resistance between DAs and antibiotics (Kampf, 2018a , b ). This is supported by a recent study of Morante et al ( 2021 ) which found no relation in Klebsiella pneumoniae isolates resistant to isopropanol and antibiotic resistances. This is contrary to de Carvalho et al ( 2020 ) who showed that Mycobacterium vaccae were more resistant to antibiotics after disinfectant exposure.…”
Section: Resistance To Disinfectants and Antiseptics And Cross-resist...supporting
confidence: 66%
“…The efflux pumps can change the structure and physiological functions of the bacterial outer membrane, and protect themselves against biocides [ 15 , 21 ]. Some multi-drug efflux pump families are able to mediate the efflux of multiple disinfectants and antibiotics at the same time, leading to cross resistance [ 22 , 23 ]. To explore the correlation of efflux pump genes with the resistance of CRKP strains to disinfectants, we detected three efflux pump genes ( oqxA , oqxB , and qacE ∆1-sul1 ) [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies are needed to understand the spectrum of Cp‐Kpn during the COVID‐19 pandemic. In Peru, there is increasing antibiotic resistance 13 in isolated patients resistant to hospital disinfectants 18 and may spread the virus in ICUs, impacting the safety of COVID‐19 patients and causing rapid mortality.…”
Section: Discussionmentioning
confidence: 99%